One-Tier System Juridical Analysis in Single-Member Company in Indonesia - Devi Atikawati; Reka Dewantara; Dyah Aju Wisnuwardhani (Budapest International Research and Critics University, 2022)
To embody the ease of doing business, the government introduced a new entity, namely a single-member company, by adhering to a one-tier system but not in line with the organs regulated in Law Number 40 of 2007 concerning Limited Liability Companies. The objective of the research is to examine the one-tier system in single-member companies in Indonesia. This research is normative-descriptive juridical research through literature study and aims to analyze the juridical implications of the one-tier system in the organs of single-member companies after the enactment of Law Number 11 of 2020 concerning Job Creation. Based on the results of the study, it is known that there are differences in the terms used in the designation of single-member company organs, and there may be concurrent positions in single-member companies, this has implications for the absence of the checks and balances principle in a company and concurrent positions in a company have the potential to cause a conflict of interest where every management action that contains a conflict of interest is categorized as an act of bad faith. Because such actions are considered as a breach of fiduciary duty and the obligation to obey the laws and regulations.